Relationship between Mutations in Dihydropteroate Synthase of Pneumocystis carinii f. sp. hominis Isolates in Japan and Resistance to Sulfonamide Therapy - Takahashi, Takashi (American Society for Microbiology, 2000)
We examined mutations in the dihydropteroate synthase (DHPS) genes of Pneumocystis carinii f. sp. hominis (P. carinii) strains isolated from 24 patients with P. carinii pneumonia (PCP) in Japan. DHPS mutations were identified at amino acid positions 55 and/or 57 in isolates from 6 (25.0%) of 24 patients. The underlying diseases for these six patients were human immunodeficiency virus type 1 infection (n = 4) or malignant lymphoma (n = 2). This frequency was almost the same as those reported in Denmark and the United States. None of the six patients whose isolates had DHPS mutations were recently exposed to sulfa drugs before they developed the current episode of PCP, suggesting that DHPS mutations not only are selected by the pressure of sulfa agents but may be incidentally acquired. Co-trimoxazole treatment failed more frequently in patients whose isolates had DHPS mutations than in those whose isolates had wild-type DHPS (n = 4 [100%] versus n = 2 [11.1%]; P = 0.002). Our results thus suggest that DHPS mutations may contribute to failures of co-trimoxazole treatment for PCP.